Exploring Stakeholder Significance and Impact at Tanjung Moco Port within the Tanjung Pinang Free Trade Zone - Muzwardi, Ady; Fera*, Mirta; Kustiawan, Kustiawan (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
The Tanjungpinang Free Trade Zone has been operational for over 15 years, but this area has yet to fully harness the potential and benefits of Free Trade Zone regulations due to the absence of a free port serving as a crucial connectivity node between the Tanjungpinang Free Trade Zone, export destinations, and the hinterland area. The aim of this research is to analyze the role of Tanjung Moco Port as a Free Port within the Tanjungpinang Free Trade Zone. This research was conducted using qualitative methods, which involved literature reviews and interviews with BP Tanjungpinang Area officials and business stakeholders operating in the Tanjungpinang Free Trade Zone. The study's findings reveal that maritime connectivity offers several advantages that align with the Tanjungpinang Free Trade Zone's development plans. Through an analysis of needs and supply chains, the study underscores the significance of Tanjung Moco Port's existence to support logistics activities. Keywords: Free Port; Free Trade Zone; Tanjung Moco; Tanjungpinang; Logistic